THU0357 Features associated with loss to follow-up in the year prior to death in patients with systemic lupus erythematosus: a retrospective analysis from a national referral centre. (12th June 2018) - Padjen, I.; Erceg, M.; Cerovec, M.; Bakula, M.; Mayer, M.; Stevanovic, R.; Anic, B.
Abstract : Background: Loss to follow-up in the year prior to death may lead to underrecognition and underreporting of systemic lupus erythematosus (SLE) as a cause of death of lupus patients. Objectives: We aimed to assess the extent and features associated with loss to follow-up in the year prior to death in a group of 90 deceased SLE patients from our tertiary centre. Methods: We retrospectively analysed 90 SLE patients (68 females) followed-up at our centre, deceased from 2002 to 2011. Patients were ≥18 years of age at death and fulfilled ≥4 classification criteria of the American College of Rheumatology (ACR). The cause and place of death were identified by matching patient data from our department's SLE registry with data from the National Death Database. Patients were considered lost to follow-up in the year prior to death (LTF) if the time span between the last visit to our centre and death exceeded 1 year. Other patients were considered to be under regular follow-up (RGF). An extensive set of parameters was compared between the LTF and RGF groups: demographics, ACR classification criteria, cumulative damage according to the Systemic Lupus International Collaborative Clinics (SLICC)/ACR index, as well as causes of death. Frequencies were compared using the chi-square and Fisher's exact test, and continuous variables using the t-test and Mann-Whitney U-test. Results: We identified 35/90 patients in the LTF group (29 females). The time span between the last visit to our centre and death of LTF patients ranged from >1 to 3 years. Compared to the RGF group, LTF patients were diagnosed at a later age (mean ±SD: 54±15 vs. 44±17 years, p=0.006), while there was no difference in disease duration (median of 11 years, IQR of 5–15 years in the RGF group vs. median of 7 years, IQR of 5–15 years in the LTF group, p=0.285). The LTF and RGF groups did not differ in the count of ACR criteria (median of 5, IQR of 4–6 vs. median of 6, IQR of 5–7, p=0.053) and cumulative damage (median damage of 3, IQR of 2–5 vs. median of 5, IQR of 3–8, p=0.068). Compared to the RGF group, LTF patients had a lower cumulative proportion of pericarditis (1/35 vs.16/55), proteinuria (10/35 vs. 30/55), hemolytic anaemia (1/35 vs. 10/55), thrombocytopenia (5/35 vs. 21/55) and Hughes syndrome (2/35 vs. 13/55) (p<0.05). Pulmonary damage and peripheral vascular damage were observed only in RGF patients (9/55 vs. 0/35, p=0.011; and 8/55 vs. 0/35, p=0.021, respectively). LTF patients also had a lower proportion of cardiomyopathy (7/35 vs. 24/55, p=0.021) RGF patients died more frequently from active lupus compared to their LTF counterparts (24/55 vs. 2/35, p<0.001), while no difference was observed between the proportions of death from infections, cardiovascular diseases, malignancies and unknown causes (figure 1). SLE was reported in death certificates of 30/55 RGF patients compared to only 11/35 LTF patients (p=0.032). Compared to the RGF group, a lesser proportion of LTF patients died in the hospital (17/35 vs. 46/55, p=0.004). Conclusions: A lower proportion of LTF patients exhibited features of active SLE over their disease course. This may have led to underrecognition of SLE as a contributor to death. References: [1] Calvo-Alen J, et al. Rheumatology2005;44:1186–9. [2] Abu-Shakra M, Novack V. J Rheumatol2012;39:458–60. Disclosure of Interest: None declared